Implementasi Manajemen Hubungan Masyarakat Dalam Pendidikan Sistem Ganda Di SMK Negeri 2 Luwu - Munir Yusuf; Firman Patawari; Taqwa; Tasdin Tahrim; Nur Alfiah Has (edujavare, 2024)
This study aims to find out how public relations management planning in dual system education (PSG) at SMK Negeri 2 Luwu; To find out the organization of dual system education public relations management at SMK Negeri 2 Luwu; To find out the implementation of public relations management in dual system education at SMK Negeri 2 Luwu; To find out the supervision of public relations management in dual system education at SMK Negeri 2 Luwu. This type of research is using a qualitative descriptive approach. The subjects in this study were principals, vice principals of public relations, students and parents, data collection techniques in the form of interviews, observation and documentation. Data analysis techniques used are processing or compiling raw data, data sorting, data coding, analysis understanding, identification, changing data, empirical interpretation, rewriting statements of meaning. The results showed that the implementation of public relations management in dual system education at SMK Negeri 2 Luwu went well. This can be seen from the efforts made starting from planning, public relations always hold meetings every time they carry out activities to discuss public relations work programs, and discuss what the community, especially parents of students, need related to student education activities. Organizing, organizing is carried out for delegation of authority and team response to its work program. The implementation, the type of public relations implementation at SMK Negeri 2 Luwu is cooperation with the business world and industry, development of expertise programs, dissemination of information. Supervision, supervising public relations activities so that they can run smoothly in accordance with what is planned, organized, and implemented.